Rigid and planar π-conjugated molecules leading to long-lived intramolecular charge-transfer states exhibiting thermally activated delayed fluorescence - Suman Kuila; Hector Miranda-Salinas; Julien Eng; Chunyong Li; Martin R. Bryce; Thomas J. Penfold; Andrew P. Monkman (Nature Communications)
Abstract Intramolecular charge transfer (ICT) occurs when photoexcitation causes electron transfer from an electron donor to an electron acceptor within the same molecule and is usually stabilized by decoupling of the donor and acceptor through an orthogonal twist between them. Thermally activated delayed fluorescence (TADF) exploits such twisted ICT states to harvest triplet excitons in OLEDs. However, the highly twisted conformation of TADF molecules results in limited device lifetimes. Rigid molecules offer increased stability, yet their typical planarity and π-conjugated structures impedes ICT. Herein, we achieve dispersion-free triplet harvesting using fused indolocarbazole-phthalimide molecules that have remarkably stable co-planar ICT states, yielding blue/green-TADF with good photoluminescence quantum yield and small singlet-triplet energy gap < 50 meV. ICT formation is dictated by the bonding connectivity and excited-state conjugation breaking between the donor and acceptor fragments, that stabilises the planar ICT excited state, revealing a new criterion for designing efficient TADF materials.